Meningkatkan Hasil Belajar Siswa Melalui Problem Based Learning SD Negeri 04 Taeh Baruah - Zainab Zainab; Iswantir Iswantir; Defi Yuslia; Wirna Wirna; Alpinadri Alpinadri; Imelda Sofia (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This research is motivated by the low learning outcomes of UPTD SDN 04 Taeh Baruah students. This study aims to improve student learning outcomes at UPTD SDN 04 Taeh Baruah through the Coopeartive Learning method The type of research used is Classroom Action Research (PTK) with the Problem Based Learning (PBL) model. The method used in the research is two cycles, namely the Coopeartive Learning method. Each cycle consists of 4 stages, namely planning, implementation/action, observation, and reflection. Each cycle consists of one meeting (3 lesson hours). The total population used was 10 people. The data collection techniques used were observation, tests and interviews. The results of this study showed an increase in student learning outcomes from pre-action, cycle I and cycle II. The learning outcomes of students in the pre-action stage were 42%, in cycle I (first) increased to 67%, in cycle II (second) also increased to 92%. Thus, a recommendation can be made that the application of the Cooperative Learning method can improve student learning outcomes in Islamic religious education material for the 2024/2025 school year.